HETEROGENEITY OF AR AND SR INITIAL ISOTOPIC COMPOSITION IN THE COEXISTING MINERALS FROM MIOCENE HYPABYSSAL GRANITOIDS IN THE CAUCASIAN MINERAL WATERS REGION - Lebedev V.A.; Chernyshev I.V.; Avdeenko A.S.; Nosova A.A.; Dokuchaev A.Ya.; Oleinikova T.I.; Gol'tsman Yu.V. (My University, 2006)
Late Miocene subalkaline granite magmatism in the Caucasian Mineral Waters (CMW) region is related to the first stage of Late Cenozoic magmatic activity in the Caucasian segment of the Alpine foldbelt. The young age and presence of uranium mineralization, as well as other factors including easy availability, promoted detailed study of these intrusions in geological, mineralogical, petrographical, geochemical, and physicochemical aspects.
Keywords: Caucasus; Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен